PP.16.29: DETAILED INFORMATION ABOUT LIFESTYLE CHANGES IMPROVES CARDIOVASCULAR RISK IN HIGH NORMAL OR GRADE I HYPERTENSIVE PATIENTS. (June 2015) - Chiotelis, I.; Rallidis, L.; Kallistratos, M.; Poulimenos, L.E.; Skyrlas, A.; Manolis, A.J.
Abstract : Objective: Only a small fraction of hypertensive patients suffers from hypertension alone. The majority of patients present overlapping risk factors and thus, assessment of total cardiovascular risk is imperative in order to improve their prognosis. According current guidelines, in high normal hypertension only life style changes are suggested while in grade I hypertensive patients, drug treatment should be considered after lifestyle changes. Risk models are used in order to identify patients who are at high risk for cardiovascular disease and benefit through preventive interventions. The aim of the study was to calculate total cardiovascular risk of enrollees based on the Greek model of SCORE (Hellenic Score) and the change in their risk after a short - term appropriate intervention (lifestyle modification). Design and method: In this study, of 212 patients with high normal or grade I hypertension were prospectively enrolled, without documented cardiovascular disease (CVD). The data were collected according to: gender, age, height, weight, smoking habits, blood pressure, total cholesterol, HDL-C, LDL-C. Patients were randomly allocated in 2 groups. The 1st group (105 patients) was provided detailed information regarding the benefits of lifestyle changes while in the 2nd group (107 patients), only brief information regarding lifestyle changes was given. In both groups, drug treatment was administrated if necessary. The total cardiovascular risk was calculated in two phases, before and after the intervention. Results: Subjects' mean age was 54 ± 12 years. Subjects who were given detailed information regarding the benefits of lifestyle changes showed a greater reduction in systolic blood pressure (from 134 mmHg to 126 mmHg p < 0.0001), total cholesterol (from 207 mg/dl to 194 mg/dl p < 0.0001), LDL cholesterol (from 126 mg/dl to 115 mg/dl p < 0.0001) and improved also the risk score (from 3.41 to 2.92 p < 0.05) and relative score (from 2.81 to 1.77 p < 0.0001). Those results were not associated with the drugs used (p = ns). Conclusions: Patients with high normal or grade I hypertension may have increased risk for CVD. Detailed information regarding lifestyle changes can improve CVD risk in those subjects and therefore improve prognosis independently from the drug regiment used.